Deset let bolonjske reforme na Fakulteti za socialno delo - Mesec, Bojana (Socialno delo, 2015)
In June 1999, the ministries of higher education from 29 European countries met in Bologna to sign an important agreement, known as the Declaration of Bologna. It initiated an important and irreversible process of harmonising various European systems of higher education: the so called Bologna Process. Its main objective is the formation of a European Area of Higher Education and the promotion of the European system of higher education on a worldwide scale in order to increase its international competitiveness. The aim was to achieve harmonization of the European university systems. In 2004, the Faculty of Social Work decided to join the process and developed new programmes on all three levels (undergraduate, master and doctoral). The process was long and difficult but also fruitful and focused. New programmes incorporated the science of social work, employment goals, social practice and students% wishes. In 2015, we now have a modern study of social work, but we know that the process is far from finished. It is only the beginning of a long journey if we want to reach the high goals from the Declaration of Bologna.
Keywords: social work; socialno delo; acreditation; Bologna Process; bolonjska reforma; kakovost študija; study quality; study reform; prenova študija; University of Ljubljana; Univerza v Ljubljani